Comparison of quality of human serum albumin preparations in two pharmaceutical products - Nakae, Hajime (Acute Med Surg, 2017)
AIM: Human serum albumin (HSA) is known for its multiple functions, such as maintenance of colloid osmotic pressure, transport of endogenous and exogenous substances, and antioxidation. The aim of this study was to measure the redox state and concentrations of β‐d‐glucan and endotoxin to compare the quality of 5% HSA preparations from two different manufacturers. METHODS: The quality of 5% HSA preparations in two different pharmaceutical products (groups A and B) was compared in terms of the percentage of reduced and oxidized albumin and the contaminant level of β‐d‐glucan and endotoxin. RESULTS: The percentage of human mercaptoalbumin in group A was significantly higher than that in group B (P < 0.01), whereas that of human non‐mercaptoalbumin‐2 in group A was significantly lower (P < 0.01). The concentration of β‐d‐glucan in group A was significantly lower than in group B (P < 0.01). CONCLUSIONS: The present findings indicate the need for quality control of HSA preparations in applications involving the use of large volumes.